2011
DOI: 10.1111/j.1476-5381.2011.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan, ramipril and their combination improve endothelial function in different tissues in a murine model of cholesterol‐induced atherosclerosis

Abstract: BACKGROUND AND PURPOSEErectile dysfunction correlates with cardiovascular disease and its common risk factors due to the development of endothelial dysfunction. Positive effects on endothelial and erectile function have been described for substances inhibiting the renin-angiotensin-system. Here, we investigated in an atherosclerosis model, whether telmisartan (angiotensin receptor blocker) and ramipril (angiotensin converting enzyme inhibitor) are equivalent or the combination of both is superior in improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…Based on the data showing the expression of ACE2 on the CC, we sought to evaluate if pharmacological increase of this enzyme would produce beneficial effects against injures induced by hypercholesterolemia. As previously observed [28,35], we found that ROS production was augmented in ApoE −/− mouse penis (Figure ), which was associated to an increased protein expression of NADPH oxidase (Figure ). Remarkably, the treatment with DIZE decreases ROS production in the CC of ApoE −/− mice to a comparable level of wild type mice (Figure A–D).…”
Section: Resultssupporting
confidence: 86%
“…Based on the data showing the expression of ACE2 on the CC, we sought to evaluate if pharmacological increase of this enzyme would produce beneficial effects against injures induced by hypercholesterolemia. As previously observed [28,35], we found that ROS production was augmented in ApoE −/− mouse penis (Figure ), which was associated to an increased protein expression of NADPH oxidase (Figure ). Remarkably, the treatment with DIZE decreases ROS production in the CC of ApoE −/− mice to a comparable level of wild type mice (Figure A–D).…”
Section: Resultssupporting
confidence: 86%
“…The relaxing effect of acetylcholine was abolished by adding N ω -nitro-L-arginine methyl ester (L-NAME, 1 μM). The presence of functional endothelium was verified by the ability of acetylcholine (10 μM) to induce more than 70% relaxation of rings precontracted with phenylephrine (1 μM) 25,26. Aortic rings without any response to acetylcholine (relaxation < 10%) were excluded from statistical analysis due to presumable damage of the endothelium.…”
Section: Methodsmentioning
confidence: 99%
“…In an animal model of hypertension‐induced ED, captopril reversed the impairment of erectile function . Accordingly, telmisartan and ramipril (ARBs and ACEi respectively), significantly improved the cavernosal endothelial function of hypercholesterolaemic mice via the reduction in oxidative stress . Moreover, in a rat model of diabetes‐induced ED, losartan treatment restored the impaired erectile function .…”
Section: Role Of Ang Ii/at1 Receptor Axis In Penile Erection Physiolomentioning
confidence: 97%